International business - Ball, Donald A. (The McGraw-Hill Companies, 2008)
A broad range of topics is dealt with, to show students the steps a business must take to go global. As the ultimate reference for the international business student, the book incorporates global examples with the worldview vignettes within the chapter. Moreover, this text does not limit its focus to huge multi-national corporations. Smaller firms are highlighted within each chapter in the Mini-MNEs boxed examples.